The Satellite Agribusiness Innovation Center in Saint Louis, Senegal - Brethenoux, Julia; Dioh, Simon; Drago, Nicola; Giddings, Steven; Olafsen, Ellen; Thaller, Jim (World Bank, Washington, DC, 2014)
The establishment of an Agribusiness Innovation Center (AIC) in Senegal takes advantage of already existing agriculture and agro-processing sectors and uses this to both identify and support a pipeline of growth enterprises that can be accelerated. The AIC initiative seeks to identify growth entrepreneurs and these are defined as entrepreneurs that can create a significant number of job opportunities while expanding markets through regional, national and export sales. Their impact is therefore much deeper than survivalist entrepreneurs who are in business to support their immediate family livelihood. Once identified, the AIC supports them to make best use of resources and market opportunities. In a phased approach, starting with the Saint Louis region, the AIC is introducing pre-incubation support that can, depending on the initial outcomes, develop into a future AIC hub being developed in each of the regions. The Saint Louis Satellite AIC (sAIC) includes the following activities: 1) establishment and awareness creation; 2) introductory entrepreneurship workshops; 3) pre-incubation enterprise development programme; 4) assessment of regional business opportunities in the region and market opportunity matching with local enterprises; and 5) initiation of incubation for selected enterprises.